Implementation of Youth Organization Leadership as Village Sustainable Development Goals - Heryanto Susilo; Gunarti Dwi Lestari; Gumpanat Boriboon (Universitas Negeri Semarang, 2024)
Karang Taruna as a social organization is an important institution for realizing community welfare. The young generation of youth organizations as future leaders have a big responsibility in developing the village and improving the community's economy. The degradation of leadership in social organizations is an indicator of a crisis of public trust. To build the character of the younger generation is through internalizing behavioral values, morals, norms, and rules to realize the vision of youth organizations to achieve village sustainable development goals (Village SDGs). The purpose of this research is to describe the implementation of youth training and maximizing village potential. This article uses a qualitative research method with a case study approach. The researchers are the key instruments from October 2022 to December 2022. The research location is in Purwosari Village, Purwosari District, Bojonegoro Regency, Indonesia. The research subjects were obtained using the snowball sampling technique. The number of research informants was seven informants consisting of five informants who were members of the youth group, one chairman of the youth group, and one village head. Primary data sources were researchers from informants who had attended training, and secondary data sources from Karang Taruna Sasana Krida Muda documents and Purwosari Village documents. Field data collection uses participant observation, in-depth interviews, and document studies. Research data analysis uses three stages, namely: data condensation, data reduction, and presentation and conclusion. The results of the study showed that: (1) youth leadership training aims to train leaders' communication skills, analysis skills on field conditions, the formation of leaders as good listeners, firm and responsible leaders, and leadership skills in making decisions; and (2) maximizing village potential through land use programs as hydroponic fruit gardens, vegetables, and “reservoir” fisheries. An education-based tourism village as a tourist destination based on local wisdom to realize village sustainable development goals (SDGs) through cross-sectoral collaboration and the formation of the character of the younger generation